Kompetensi dan Disiplin Kerja Terhadap Kinerja Pegawai pada Badan Kesatuan Bangsa dan Politik Kota Bandung - Clarissa Anabella Mumtaz; Puspita Wulansari (Journal of Management and Bussines (JOMB), 2023)
This research aims to determine the influence of competency and work discipline on employee performance at BAKESBANGPOL Bandung City. The research method used is quantitative. The research results show, a) the competency variable on employee performance has a significance level of 0.000 < 0.05 and tcount 4.833 > 2.002; b) the work discipline variable on employee performance has a significance level of 0.000 < 0.05 and tcount 5.475 > 2.002; c) the competency and work discipline variables on employee performance have a significance level of 0.000 < 0.05 and Fcount 31.761 > 3.159; d) coefficient of determination (R2) of 0.527, meaning that the percentage contribution of the influence of competence and work discipline on employee performance at BAKESBANGPOL Bandung City is 52.7% and the remaining 47.3% is influenced by other factors not selected for research. Conclusion, a) partially competency has a positive and significant effect on employee performance at BAKESBANGPOL Bandung City; b) in particular work discipline has a positive and significant effect on employee performance at BAKESBANGPOL Bandung City; c) simultaneously competency and work discipline have a significant positive influence on employee performance at BAKESBANGPOL Bandung City. Keywords: Competence, Work Discipline, Employee Performance